Unique organization of photosystem II supercomplexes and megacomplexes in Norway spruce. (1st August 2020) - Kouřil, Roman; Nosek, Lukáš; Opatíková, Monika; Arshad, Rameez; Semchonok, Dmitry A.; Chamrád, Ivo; Lenobel, René; Boekema, Egbert J.; Ilík, Petr
SUMMARY: Photosystem II (PSII) complexes are organized into large supercomplexes with variable amounts of light‐harvesting proteins (Lhcb). A typical PSII supercomplex in plants is formed by four trimers of Lhcb proteins (LHCII trimers), which are bound to the PSII core dimer via monomeric antenna proteins. However, the architecture of PSII supercomplexes in Norway spruce[ Picea abies (L.) Karst.] is different, most likely due to a lack of two Lhcb proteins, Lhcb6 and Lhcb3. Interestingly, the spruce PSII supercomplex shares similar structural features with its counterpart in the green alga Chlamydomonas reinhardtii [Kouřil et al . (2016) New Phytol . 210, 808–814]. Here we present a single‐particle electron microscopy study of isolated PSII supercomplexes from Norway spruce that revealed binding of a variable amount of LHCII trimers to the PSII core dimer at positions that have never been observed in any other plant species so far. The largest spruce PSII supercomplex, which was found to bind eight LHCII trimers, is even larger than the current largest known PSII supercomplex from C. reinhardtii . We have also shown that the spruce PSII supercomplexes can form various types of PSII megacomplexes, which were also identified in intact grana membranes. Some of these large PSII supercomplexes and megacomplexes were identified also in Pinus sylvestris, another representative of the Pinaceae family. The structural variability and complexity of LHCII organization in Pinaceae seems to be related to the absence of Lhcb6 and Lhcb3 in this family, and may be beneficial for the optimization of light‐harvesting under varying environmental conditions. Significance Statement: Norway spruce is known to lack two Lhcb proteins (Lhcb6 and Lhcb3), and its photosystems II (PSII) are organized into supercomplexes, which are similar to those observed in the green alga Chlamydomonas reinhardtii . Here we show that PSII in spruce can bind even more light‐harvesting complexes than PSII in Chlamydomonas, which makes it the largest PSII supercomplex ever observed, and that spruce supercomplexes can form various megacomplexes, detectable also in intact grana membranes.